Canal lock variable speed hydropower turbine design and control. Issue 14 (24th September 2018) - Zhang, Jian; Leontidis, Vlasios; Dazin, Antoine; Tounzi, Abdelmounaim; Delarue, Phillipe; Caignaert, Guy; Piriou, Francis; Libaux, Antoine
Abstract : The design of a novel submerged hydraulic turbine for producing electricity by converting the available hydropower on canal locks during raising and lowering ships, but with the minimum overall impact on the facility, is being considered. The hydraulic head in such applications is low (few metres) and varies over time (from its maximum value down to zero) resulting in a low potential conversion of hydraulic head in electrical energy. The study involves the modification of the hydraulic transient system, the design and performance estimation of a hydraulic turbine. Based on the performance curves, a permanent magnet Vernier generator is designed. The models of the hydraulic turbine and generator are added to the system model and simulation results of the whole system are presented.